Studi Eksperimental Unjuk Kerja Motor Diesel Putaran Stasioner dengan Campuran Bahan Bakar Biodiesel Buah Nyamplung - Yuliyanti Dian Pratiwi; Sutarno; Warso (Accurate: Journal of Mechanical Engineering and Science, 2021)
The recent development of technology and the continuous development of human lifestyle have resulted in the increasing of the need for energy, so that the availability of energy from non-renewable fossil fuels is decreasing, and it is even predicted that it will run out over time. One of the most prospective vegetable oil resources to be used as a raw material for biodiesel is product from the processing of nyamplung seeds (Calophyllum Inophyllum L). Due to nyamplung seed oil is not included in the category of primary food needs, so its usage as a biodiesel will not interfere with human food needs. The purpose of this research is to find out how much torque and sfc power to the mixture of biodiesel fuel from nyamplung fruit. This research used experimental studies with research that has been done to produce Power, Torque, and Sfc from a mixture of 20% of 1.72kW, 10,955Nm and the value of increase down 10.08%. Percentage of 30% 1,692kW, 10,777N.m and the value increase / decrease -1.09%. The percentage of 40% 1,719kW, 10,949N.m and the rate is up / down 5.77% for Dexlite. Percentage of 20% 1,722kW, 10,968N.m and 4.63% increase / decrease value. Percentage of 30% 1,710kW, 10,891N.m and value increase / decrease 6.52%. The percentage of 40% 1,722kW, 10,968N.m and the increased value by 5.95% for Pertamina DEX.